Who owns the Atoms? Nanotechnology and Intellectual Property Rights - Tomás Javier Carrozza; Susana Silvia Brieva (Íconos)
In Latin America, under the premise of enhancing economic competitiveness, there has been an exponential increase in investments in the development of nanotechnologies. In this context, the discussion about intellectual property rights with regards to nanotechnology is increasingly central to public debates. However, in comparison with the attention that this issue has attracted in both public and private contexts, there has been little academic analysis published on property rights and nanotechnology. This article problematizes the application of property rights in the development of nanotechnologies through a critical literature review of the existing literature on the topic. From this analysis, the key issue of the restrictions imposed on the application of patents on ‘first generation’ products is analyzed. This question pits those who claim rights to royalties to recoup R and D investments made to develop these technologies against those who argue for open access to science and technology.